2019
DOI: 10.2174/1875036201912010050
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Applications for the Promotion and Support of Healthy Nutrition and Physical Activity Habits: A Systematic Review, Extraction of Features and Taxonomy Proposal

Abstract: Background: Mobile applications can be used for the monitoring of lifestyles and physical activity. It can be installed in commodity mobile devices, which are currently used by different types of people in their daily activities worlwide . Objective: This paper reviews and categorizes the mobile applications related to diet, nutrition, health, physical activity and education, showing the analysis of 73 mobile applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
5
0
2
Order By: Relevance
“…Thus, all apps that appeared in our search, regardless of their rating, were included. However, most apps-regardless of their operating system-had a high rating; 47.5% of the apps in the sample had a rating of 4.5 or above out of 5, which is similar to the ndings of Villasana et al, who reported that 51% of apps had a rating above 4.5 [22]. Notably, previous studies included only apps rated 4 or higher [19] [22].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, all apps that appeared in our search, regardless of their rating, were included. However, most apps-regardless of their operating system-had a high rating; 47.5% of the apps in the sample had a rating of 4.5 or above out of 5, which is similar to the ndings of Villasana et al, who reported that 51% of apps had a rating above 4.5 [22]. Notably, previous studies included only apps rated 4 or higher [19] [22].…”
Section: Discussionsupporting
confidence: 78%
“…Villasana et al classi ed the purpose of apps as diet and nutrition, health, education, or physical activity. Fifty-two percent of the apps were related to "diet and nutrition", 25% were related to "health", 11% were related to "education", and 12% were related to "physical activity" [22]. These differences might be due to the exclusion criteria used in this review, which involved excluding any app that exclusively targeted physical activity, general health, or education.…”
Section: Discussionmentioning
confidence: 99%
“…Given that mobile applications are used to control lifestyle habits [ 33 , 34 ], and that young people use mobile devices [ 35 ] and mobile applications [ 36 ] frequently, a systematic review was carried out to study which mobile applications are most used by people who use devices with the Android operating system and which are related to diet, nutrition, health, and physical activity [ 37 ]. Mostly, the mobile applications are related to diet and nutrition, and the features that were most present were weight, height, age, sex, goals, calculation of necessary calories, diet diary, food database and its calories, calories burned, and the calculation of calorie intake.…”
Section: Methodsmentioning
confidence: 99%
“…Another study also verified that using Fitbit devices may benefit increasing the level of PA during recreational activities [ 74 ]. The mobile applications for this subject are more related to the measurements of weight, height, age, gender, goals, and calories needed for calculations, diet diaries and food databases including calories, calories burned and calorie intake [ 75 ].…”
Section: Discussionmentioning
confidence: 99%